Study of Morbidity Pattern, Activities of Daily Living and Health Seeking Behavior among Rural Elderly in Jammu District - Bala, Kiran; Sahni, Bhavna; Kumar, Tejinder; Sangral, Rimpi (National Journal of Community Medicine, 2018)
Introduction: Elderly are the fastest growing segment of popula- tion due to demographic transition. This study was conducted to assess the morbidity pattern, health seeking behaviour and func- tional status of geriatric age group using Katz index. Methodology: Community based cross sectional study was con- ducted among elderly residing permanently in two villages. Per- sonal interview, general & clinical examinations were carried out. ADL scale was used to measure the functional status of elderly. Results: Out of 200 study subjects, 51.5% were males and 48.5% were females, 53.5% males and females were young old followed by middle old 35.5% and oldest old 11%. The prevalence of hyper- tension, diabetes and cataract was 56.5%, 52.0% and 40.0% respec- tively and significant association with gender was found for diabe- tes, hypertension and CVD with gender. Dependency assessed by ADL, showed that 16.0% were partially/ totally dependent and total dependency increased with age. Conclusion: Secondary prevention of health problems of elderly and screening of functional disabilities by primary care physicians should be prioritized.